2022
DOI: 10.3390/antibiotics11050607
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Immunomodulatory Effects of Selected Chemokine and Antimicrobial Peptide on Cytokine Profile during Salmonella Typhimurium Infection in Mouse

Abstract: The antimicrobial and immunomodulatory capacities of the peptide Css54 and the chemokine MCP-1 were tested. The first, a peptide isolated from the venom of the scorpion Centruroides suffusus suffusus was synthesized chemically. In contrast, the second is a monocyte chemoattractant expressed as a recombinant protein in our lab. It was observed in vitro that Css54 inhibited the growth of Salmonella enterica serovar Typhimurium (6.2 µg/mL). At high concentrations, it was toxic to macrophages (25 µg/mL), activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In this study, IL-1β, IL-6 and TNF-α serum levels dropped significantly in infected mice following GCTA treatment. Although there was no significant change in IL-10, it showed an upward trend after infection which was reduced by GCTA, consistent with previous results [ 46 ]. These findings suggest that GCTA modulates the inflammatory response and may create an anti-inflammatory environment, which could be further supported by further study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, IL-1β, IL-6 and TNF-α serum levels dropped significantly in infected mice following GCTA treatment. Although there was no significant change in IL-10, it showed an upward trend after infection which was reduced by GCTA, consistent with previous results [ 46 ]. These findings suggest that GCTA modulates the inflammatory response and may create an anti-inflammatory environment, which could be further supported by further study.…”
Section: Discussionsupporting
confidence: 92%
“…Two AMPs (IK12 and TS10) were compared for their efficacy against S. enterica in fish, and the results demonstrated that AMP (IK12) exhibited a significant inhibition zone (20 ± 1 mm) against S. enterica at a concentration of 625 µg/mL, while concentrations of 1000 µg/mL and 2500 µg/mL decreased the Salmonella load up to 6 log [326]. In addition to this, the treatment of S. Typhimurium-challenged mice with AMP (Css54) demonstrated that Css54 can inhibit S. Typhimurium growth at a concentration of 6.25 µg/mL, while complete bactericidal activity can be obtained at a concentration of 25 µg/mL [327]. Similarly, supplementing S. Enteritidis-challenged female laying chicks with two different doses of AMP (Ctx(Ile 21 )-Ha) at the rate of 20-40 mg/kg feed for 28 days revealed a reduced mortality rate in young chickens by 69%; however, no difference in the mortality rate was observed even after increasing the Ctx(Ile 21 )-Ha dose concentration [328].…”
Section: Antimicrobial Peptidesmentioning
confidence: 97%
“…Cytokines are proteins of ≈80 kDa (≈2.8 nm) and are typically positively charged. [52][53][54][55][56][57][58][59] As the size of the MOF-808 pore (1.8 nm) would hinder cytokine adsorption, we investigated the surface charge of the MOF-808 crystals. The surface charge was measured by the zeta potential after dispersing MOF-808 crystals in PBS under different pH conditions.…”
Section: Cytokine Removal By Mof-808 Crystalsmentioning
confidence: 99%